How Wind Affects Homes - Kathleen C. Ruppert; Hal S. Knowles, III; Karla A. Lenfesty (EDIS)
ABE-379, a 2-page fact sheet by Kathleen C. Ruppert, Hal S. Knowles, III, and Karla A. Lenfesty, is part 6 in the Education + Action = Wind Damage Mitigation series. It discusses the science behind how wind affects buildings. Published by the UF Department of Agricultural and Biological Engineering, April 2007.